1975
DOI: 10.1007/bf00429913
|View full text |Cite
|
Sign up to set email alerts
|

Diabetogenic effect and inhibition of insulin secretion induced in normal rats by ammonium infusions

Abstract: Summary. In order to explain the abnormalities of glucose metabolism previously observed in patients with blood ammonia elevation, the effect of a transitory hyperammonemia on I. V. glucose tolerance was investigated in rats. An I. V. glucose tolerance test was performed in 3 groups of 15 rats 60 min after the beginning of a 95 rain infusion of either a 2 ml isotonic NaC1 solution (control group) or ammonium acetate solutions at low (0.50 gmol/kg/min. NI-I4+ ) or high doses (1.70 ~tmol/kg/min NH4+ ). The "high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
1

Year Published

1978
1978
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 28 publications
(32 reference statements)
0
6
1
Order By: Relevance
“…The latter phenomenon was '45Ca UPTAKE (percent) DISCUSSION The present findings confirm that NH4+ is a potent inhibitor of insulin release. Previous reports have indicated that 0.1-1.0 mM NH4+ inhibits glucose-stimulated insulin release both in vitro using pieces of pancreas removed from the golden hamster (11) and in vivo in rats (13) and men (12) infused with NH4+. A role for NH4+ in the abnormality of islet function seen in cirrhotic patients (12,31) was also documented.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter phenomenon was '45Ca UPTAKE (percent) DISCUSSION The present findings confirm that NH4+ is a potent inhibitor of insulin release. Previous reports have indicated that 0.1-1.0 mM NH4+ inhibits glucose-stimulated insulin release both in vitro using pieces of pancreas removed from the golden hamster (11) and in vivo in rats (13) and men (12) infused with NH4+. A role for NH4+ in the abnormality of islet function seen in cirrhotic patients (12,31) was also documented.…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, we have used NH4+, which is known to lower the concentration of reduced pyridine nucleotides in liver cells, by regulating the activity of glutamate dehydrogenase (8)(9)(10). Previous reports have already indicated that NH4+ is an inhibitor of insulin release (11)(12)(13). However, to our knowledge, the mode of action of NH4+ upon islet function had not as yet been explored in any great detail.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperammonaemia itself cannot be considered as playing a role in the increase of TSH release. Effectively the action of the ammonium ion has to be assimilated to that of catecholamines (Schlienger et al 1975) which are antagonists of the TRH action (Burrow et al 1977). Thus, portosystemic shunts, the resulting hyper¬ ammonaemia and the hepatic encephalopathy which often follows them, are factors which can affect TRH-induced TSH release in cirrhotics.…”
Section: Discussionmentioning
confidence: 99%
“…Greater degrees of acute acidemia might have lent significance to the trend toward increases in plasma potassium levels despite the complicating hyperinsulinemia. Second, infusion of ammonium salts inhibits insulin release independent of the associated acidosis (11)(12)(13). Thus interpretation of the effects of the acute NH 4 Cl load on the plasma insulin levels of the normal volunteers studied becomes even more difficult.…”
mentioning
confidence: 99%